Penerapan Media Komik Strip dalam Keterampilan Membaca Kalimat Sederhana Bahasa Jerman Kelas XII SMAN 1 Menganti - Jarita Dewi, Annisa Kulsum; Dwi Imroatu Julaikah (LATERNE, 2024)
A preliminary observation conducted with the German language teacher at SMAN 1 Menganti on February 12, 2024, revealed that the low reading skills of Class XII students at SMAN 1 Menganti were due to the lack of variety in the use of media during German language learning activities. Therefore, comic strips were deemed necessary as a supporting medium and an alternative tool for German language learning. This study aims to examine the implementation of comic strip media and the learning outcomes of German reading skills among Class XII students at SMAN 1 Menganti. The research method used was descriptive qualitative. The results of this study indicated an improvement in the reading skills of Class XII students at SMAN 1 Menganti. This was evidenced by the observation analysis results, with a percentage of 62.5% in the first meeting and 95.83% in the second meeting. Additionally, the learning outcomes showed that 24 students met the minimum competency standard (KKM) during the first meeting, while 28 students achieved the standard during the second meeting. Thus, implementing comic strip media can serve as an effective alternative tool for German language learning. Keywords: Reading Skills, Comic Strips, Learning Outcomes, German Language.